(untitled) (Revista Contexto & Educação, 2022)
The cell is constituted as the nuclear element of the organization principle, being the basic unit and the smallest part of living beings. In the historical development of the cell concept, we aim to make explicit the interrelationship between the ways of doing Science and the ways of teaching and learning biological concepts. This research has a theoretical character and is based on the foundations of historical-dialectical materialism and developmental teaching. We demonstrate the contribution of conceptual thinking to the teaching and learning process and to human development. We conclude by ratifying the need for the teaching of the concept of a cell to be carried out in a more organic way when doing scientific, evidencing its relationship with the content historically produced by humanity.